IMMUNOHISTOCHEMICAL METHOD OF TREATING DIABETES WITH THE EFFECT OF MORPHOLOGICAL INDICATORS ON THE ORGANISM OF EXPERIMENTAL ANIMALS - Sabirova Dildora Ravshanovna; Akbarova Mavluda Nodirbek kizi; Suyunov Akbar Tursunali ugli; Abduvosieva Mushtari Ismoil kizi; Saparaliev Umijon Hassan ugli; Tohirov Tolibjon Komiljon ugli (Journals Park Publishing, 2022)
This article is written about the study of the effect of diabetes on the organism of experimental animals by the immunohistochemically method of its effect on morphological indicators. The article is mainly written about the causes of diabetes mellitus and the fight against diabetes mellitus.
Keywords: origin of sugar, different levels, metabolism